Corruption in the digital bureaucratic service system (media studies in disclosure of corruption cases) - Nunung, Ai; Latifah, Latifah; Fatihah, Dian Candra (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Corruption still occurs even though the bureaucracy has transformed into a digital service system. Lately, the trend has become more rampant, involving all elements of service from the central to the regions, from high-ranking officials to field officers. Digitalization, which was initially implemented as a formula for preventing corruption, still opens wide gaps to be penetrated. The digital system that has been implemented has not been effective in preventing and eliminating the corrupt mentality of service delivery personnel. The digital era, which should be a moment of clean, open and responsible bureaucratic change, still has a long way to go. Based on that fact, this study aims to determine digitalization in bureaucratic services in preventing corruption. The method used in this study is descriptive qualitative, with media analysis studies to obtain data spread across three credible national online media networks. The results of the study show that corruption cases are still rife even though bureaucratic services have been transformed into a digital service system. In the implementation of the bureaucratic system, the media plays a very vital role as part of enforcing corruption laws and encouraging service personnel to act in a manner that is trustworthy, honest and responsible for their work.